ANALYSIS OF LIQUIDITY RATIOS AGAINST PROFITABILITY RATIOS (ROA) AT PT. MAYORA TBK. LISTED ON THE INDONESIAN STOCK EXCHANGE - Prayoga, Oka; Hamdan, Hamdan; Rizal, Rusma (Jurnal Manajemen, 2024)
This study aims to determine the analysis of the liquidity ratio (current ratio, quick ratio, and cash ratio) to the profitability ratio (return on assets) at PT MAYORA TBK listed on the Indonesia Stock Exchange for the period 2019-2023. The analysis technique used is descriptive analysis with the ratio analysis method. In this study, the current ratio value of 315% is greater than the general standard for similar industries, which is only 200%, while the Quick Ratio performs well and is satisfactory in financial terms because its average of 248% has exceeded the industry standard of only 150%, the Cash Ratio has an average value of 81% higher than the general standard for similar industries, which is 50%, and ROA can be concluded to be in accordance with the standard. PT Mayora Tbk exceeds 5%, indicating the company's ability to generate profit on sales can be said to be good because the average ROA value in this period reached 13%; therefore, the company's performance is quite satisfactory and is considered stable in 2019-2023.